The relationship of brand image and service quality on student loyalty: a case of MY-K, KKTM Sri Gading / Nurul Syafika Mohd Nasir - Mohd Nasir, Nurul Syafika (Faculty of Business and Management, 2018)
The study is to examine the relationship of brand image and service quality towards student loyalty in purchasing at in-campus mart at university which is My-K Kolej Kemahiran Tinggi Mara (KKTM) Sri Gading located at Batu Pahat, Johor. To perform this objective, the research has extracted three variables. A questionnaire with Likert type questions was used to collect the data. The samples of this study are the students Semester 1 until Semester 5 from all the courses in KKTM Sri Gading. The sampling technique used is proportionate stratified random sampling. The data then was analysed by using Statistical Package for the Social Sciences (SPSS). The finding of this research shows that the brand image (in-campus mart) and service quality plays an important role to the student loyalty as the students are their customer in their business. The study indicates that there is positive relationship between the two independent variables; brand image and service quality and student loyalty as the dependent variable.